Dielectric properties of low temperature sintered LiF doped BaFe0.5Nb0.5O3 - Intatha U. (2014)
Sintering of BaFe0.5Nb0.5O3:BFN requires the use of high temperatures to achieve satisfactory densification of this material. The aim of this study is to determine the effect of LiF on the sintering and electrical properties of BFN ceramics (the LiF was added as a sintering agent). The results show that LiF lowers the sintering temperature by 150-200 °C without affecting the formation of BFN. Ceramics doped with 2-3% LiF show optimum densities of about 93-94% of the theoretical value when sintered at low temperatures (1000-1100 °C). Samples containing 2-3% LiF show the following dielectric behaviour. The dielectric constant curves are very broad over a wide temperature range, with room-temperature values of 7154 in the 2% LiF sample and 2527 in the 3% LiF sample. The dielectric constants gradually increase up to 300 °C to values of about 38,862 in the 2% LiF sample and 40,471 in the 3% LiF sample. Furthermore, the addition of 2-3% LiF to BFN causes a reduction in the room-temperature dielectric loss from 4.29 in undoped BFN to less than 1.2 for LiF-containing samples. © 2006 Elsevier B.V. All rights reserved.